Exploring the Potential of Yoga as a Complementary Therapy for Polycystic Ovarian Syndrome (PCOS) - Kumalasari, Anatalya Diah Ayu; Faiza, Agyta Hanifa; Husodho, Gabriela Valencia Putri; Kesoema, Tanti Ajoe (Faculty of Medicine, Universitas Diponegoro, 2025)
Polycystic ovarian syndrome (PCOS) is an endocrine and metabolic disorder that is most commonly experienced by women. This condition can reduce the quality of life because it can affect physical, psychological, emotional, social, and financial. The first-line and safest therapy for PCOS is lifestyle changes. One of them is doing physical activity. Yoga as one of the low-intensity physical activities has the potential as a complementary therapy for PCOS. This study implements a systematic review with qualitative analysis method. A literature search was done using the search engines PubMed, Science Direct, and Proquest by setting inclusion criteria and exclusion criteria. Yoga is a sport that can be done by everyone because it does not require fitness and flexibility at a certain level. Some of the mechanisms of yoga as complementary therapy for PCOS are the optimization of the autonomic nervous system, regulation of the endocrine system, reduction of stress levels, and balancing of neural hormones. Previous research has shown that yoga can improve various aspects in PCOS women such as anthropometric parameters, menstrual cycle, ovarian morphology, biochemical markers, hormones, cardiovascular, and psychiatric conditions. Yoga can improve various aspects including anthropometric parameters, menstrual cycle, ovarian morphology, biochemical markers, hormones, cardiovascular, and psychiatric conditions.